STRATEGI WALI KELAS DALAM MEMBENTUK AKHLAK PESERTA DIDIK DI KELAS V UPT SPF SD NEGERI SUDIANG KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Yulia; Wahid , Abdul; Musbaing , Musbaing (ALENA : Journal of Elementary Education, 2024)
This study aims to determine the homeroom teacher's strategy in shaping the morals of students in class V UPT SPF SD Negeri Sudiang and the inhibiting and supporting factors in shaping the morals of students in class V UPT SPF SD Negeri Sudiang. The method used is qualitative with data collection techniques used namely by observation, interviews, questionnaires, test sheets and documentation. Based on the research results of the homeroom teacher's strategy in shaping the morals of students in class V UPT SPF SD Negeri Sudiang, Biringkanaya District, Makassar City. Shows that the homeroom teacher's strategy in shaping the morals of students in class V UPT SPF SD Negeri Sudiang, has several strategies in shaping the morals of students in class V, including: Habituation, exemplary, Targhib Wa Tarhib and giving advice. Factors that inhibit the homeroom teacher in shaping the morals of students in class V, namely: from the background and awareness of each individual self and from student association and from family environmental factors (parents), school environment and also from the community environment. The supporting factors are coming from good individual personalities and with good cooperation between the homeroom teacher and the parents of the students.